A statistical comparison of VHF techniques to study clear-air vertical velocities in the lower atmosphere using the Jicamarca radar - Chau Chong Shing, Jorge Luis (1998)
We compare two types of VHF vertical velocity measurement techniques using a special configuration of the Jicamarca 50-MHz radar antenna. Zenith (vertically directed single-beam) techniques and spaced antenna (SA) techniques are compared using a 54-hour concurrent data set. We compare two different zenith techniques using different antenna beam widths (0.85° and 3.5°). In addition, we compare vertical velocities measured by a “quasi” Doppler beam swinging (QDBS) technique and a SA approach that incorporate either “inferred” or “corrected” vertical velocities. All of the results are compared in terms of statistical basis. Results are presented for both quiet (low wind, low variability) and active (high wind, high variability) conditions. We use the results of the narrow-beam zenith technique as a reference profile and discuss its validity as a reference. Our comparisons show that relative to the reference, (1) the use of corrected values (i.e., correcting for horizontal leakage) gives better results than the wide-beam zenith technique, although mean differences of ∼−3 and ∼4 cm s−1 are still observed below 12 and above 15 km, respectively, (2) QDBS results give the closest mean value agreement of all the techniques, and (3) most of the vertical velocity discrepancies are seen as variations in the mean values.